Britain, World War 2 & the Sama Samajists : a study of the documents contained in the secret files maintained by the Public Record Office, London - Great Britain. Public Records Office (Colombo : Young Socialist Publication, 1996)
Documents, relating Britain's persecution of Sinhalese anti-war freedom fighters, released by the Public Records Office, London.
"These papers reveal how in 1940-42 the British imperial government persecuted, suppressed, and incarcerated the leaders of the Lanka Sama Samaja Party, because of their opposition to the War"--Cover.
Keywords: Lanka Sama Samaja Party -- History; World War, 1939-1945 -- Sri Lanka; Sri Lanka -- Politics and government